A novel global reaction modeling approach considering the effects of pressure on pyrolysis of n-decane at supercritical pressures. (1st March 2021) - Wang, Yusen; Jiang, Pei-Xue; Zhu, Yinhai
Highlights: Effects of pressure on supercritical pyrolysis of n-decane are investigated. The formation of liquid products is preferred at higher pressures. A novel global reaction modelling approach is proposed for hydrocarbon fuels. Stoichiometric coefficients are expressed as functions of fuel conversion and pressure. The new model predicts pyrolysis accurately at both low and high pressures. Abstract: Pressure is one of the key factors in pyrolysis of hydrocarbon fuels at supercritical pressures, which changes the relation between the product distribution and fuel conversion. However, reaction model with both high accuracy and efficiency to predict pressure effects is lacking. A comprehensive experimental investigation of pressure effects on supercritical pyrolysis of n-decane in the pressure range of 3–7 MPa and temperature range of 560–670 °C is presented. The formation of liquid products is preferred at higher pressures. Gas and liquid products of n-decane pyrolysis can be categorized into three and four types, respectively, according to the formation characteristics. Results show that pressure had more profound effects on the formation of most products without C–C double bonds or benzene rings in their molecular structures (i.e., C3 –C9 n-paraffins or cycloparaffins). A novel global reaction modeling approach was presented to solve the effects of both pressure and secondary reactions on pyrolysis of hydrocarbon fuels, in which the stoichiometric coefficients of each product are expressed as binary functions of fuel conversion and pressure. The proposed model was implemented in a computational fluid dynamics (CFD) simulation to predict the n-decane pyrolysis coupled with flow and heat transfer. The results show that the model predicts n-decane pyrolysis more accurately at both low and high pressures. This study can help design regenerative cooling systems with high accuracy and efficiency for engineering applications.